Design and Evaluation of a Memory-Recalling Virtual Reality Application for Elderly Users - Anastasiadou, Zoe; Dimitriadou, Eleni A.; Lanitis, Andreas (My University, 2024)
Virtual reality (VR) can be useful in efforts that aim to improve the well-being of older members of society. Within this context, the work presented in this paper aims to provide the elderly with a user-friendly and enjoyable virtual reality application incorporating memory recall and storytelling activities that could promote mental awareness. An important aspect of the proposed VR application is the presence of a virtual audience that listens to the stories presented by elderly users and interacts with them. In an effort to maximize the impact of the VR application, research was conducted to study whether the elderly are willing to use the VR application and whether they believe it can help to improve well-being and reduce the effects of loneliness and social isolation. Self-reported results related to the experience of the users show that elderly users are positive towards the use of such an application in everyday life as a means of improving their overall well-being.
Keywords: virtual reality; application design; elderly users